A Rare Case Of Kikuchi-Fujimoto Disease Displaying Chromosomal Abnormality. (28th October 2020) - Zhang, Y; Ding, L; Aftab, L; Rushton, P
Abstract: Introduction/Objective: Histiocytic necrotizing lymphadenitis, also known as Kikuchi-Fujimoto disease (KFD), is a rare and benign self-limiting process primarily affecting 20 35-year-old Asian women with spontaneous remission after weeks to months of illness. Although the involvement of T cell-mediated immune response, infections, and HLA class II gene have been proposed as possible etiologies, the detailed pathogenesis has not been elucidated. Very few literatures exhibited KFD displaying chromosomal abnormality such as t(2:16). Methods: Here, we report a rare case of KFD with novel karyotype abnormalities in a 24-year-old African American male. It presented as painless cervical lymphadenopathy for one month without fever, night sweats, or weight loss. An excisional biopsy of the lymph node (LN) was performed. Results: Tissue culture for bacteria and flow cytometry of the LN were negative. Histopathology revealed numerous pale circumscribed foci composed of lymphocytes, histiocytes, plasmacytoid dendritic cells, and abundant karyorrhectic debris in the background of coagulative necrosis. No neutrophils or hematoxylin bodies are seen. Immunohistochemical studies showed CD3+/CD4+ T lymphocytes, CD68+ histiocytes, and CD123+ plasmacytoid dendritic cells. Abnormal karyotype was observed as: 46, XY, del(6) (q?16q?22). Conclusion: We present this case to demonstrate that 1. Although KFD is most prevalent in young Asian females, it may occur in both genders and other ethnical groups and perhaps represents an underdiagnosed process. 2. KFD can mimic a variety of diseases such as rheumatologic, infectious, and hematologic malignancies; a thorough workup including serology, culture, and flow cytometry is needed to exclude serious diseases such as systemic lupus erythematosus and malignancy to render an early diagnosis which may avoid unnecessary diagnostic and therapeutic interventions. 3. Cytogenic abnormalities, although observed in many malignancies, should not be used as a sole determinant of malignancy, and the interpretation needs to be in a relevant clinical and histopathological context in a multidisciplinary setting to avoid misdiagnosis and inappropriate treatment.